Persepsi Mahasiswa dan Dosen tentang Bahasa Inggris sebagai Bahasa pengantar: Studi Kasus Pendidikan Tinggi Indonesia - Ahmad Husein Nst; Rahmah Fithriani (ELTIN Journal, 2023)
English Medium Instruction is teaching in English, where the country's first language is not English. The internationalization of education and educational competence that makes campuses compete in their teaching and learning process, one of which is in the language of instruction. The purpose of this research is to investigate the perceptions of students and lecturers in higher education on medium instruction. This study used descriptive qualitative methods approach with an emphasis on qualitative data, with 60 students and 3 lecturers as respondents in this study. Questionnaires and interviews were used as tools to collect data from the respondents. The results of this study show that students and Lecturers had positive perception towards the use of English Medium Instruction. Students agreed that the use of English as a teaching medium can train their skills in English. The use of English in today's world of work means that everyone must learn English. Likewise with lecturers who make them challenged by teaching in English. The thing that is often faced by students and teachers in the process of learning to catch up with them is the lack of and understanding of vocabulary.